Prevalence and pattern of anemia in the second and third trimester pregnancy in Western Rajasthan - Rawat, Kiran; Rawat, Narendra; Mathur, Navgeet; Mathur, Medha; Chauhan, Nitesh; Kakkar, Rahul; Tinna, Rajat (International Journal of Research in Medical Sciences, 2016)
Background: Anemia in pregnancy is related to maternal-fetal morbidity and mortality. In developing countries like India it is important to study prevalence and pattern of anemia in pregnancy especially in the region with higher maternal mortality rate like western Rajasthan. The main objective was to study the prevalence and pattern of anemia in second and third trimester pregnant females in western Rajasthan. Methods: In this cross sectional study females with second and third trimester pregnancy were evaluated for presence of anemia with its morphological type and severity. Results: 17,552 second and third trimester pregnant females were evaluated and prevalence of anemia was found 48.4%. The percentages of mild, moderate and severe anemia were 35.1%, 51.3% and 13.4% respectively. Most common morphological type was microcytic hypochromic anemia (51%) followed by normocytic normochromic anemia (32%), dimorphic anemia (13%) and macrocytic anemia (4%). Conclusions: There is high prevalence of anemia in pregnant females. This warrants the need of proper prophylaxis and early diagnosis of anemia in pregnancy to minimize the maternal-fetal morbidity and mortality.